Programmable Syringe Pump for Selective Micro Droplet Deposition - Erry Dwi Kurniawan; Alwin Adam; Muhammad Ichlasul Salik; Paulus Lobo Gareso (Jurnal Elektronika dan Telekomunikasi, 2019)
Micro/nanopatterns with micro deposition techniques have been used in various applications such as flexible electronic devices, biosensing, and biological tissue engineering. For depositing a small size of droplets that can be controlled, structured and patterned precisely is a very important process for microfabrication. In this study, we developed a low cost and simple system for fabricating micro/nanostructure by a selective micro deposition process using a syringe pump. This method is an additive fabrication method where selective droplet materials are released through a needle of the syringe pump. By translating the rotating stepper motor into a linear movement of the lead screw, it will press the plunger of the syringe and give a force to the fluid inside the syringe, hence a droplet can be injected out. The syringe pump system consists of a syringe, the mechanical unit, and the controller unit. A stepper motor, the lead screw, and the mechanical components are used for the mechanical unit. Arduino Uno microcontroller is used as the controller unit and can be programmed by the computer through GUI (Graphical User Interface). The input parameters, such as the push or pull of flow direction, flow rate, the droplet volume, and syringe size dimension can be inputted by the user as their desired value via keypad or the computer. The measurement results show that the syringe pump has characteristics: the maximum average error value of the measured volume is 2.5% and the maximum average error value of the measured flow rate is 14%. The benefits of a syringe pump for micro deposition can overcome photolithography weaknesses, which require an etching and stencil process in the manufacture of semiconductors. Combining two or more syringes into one system with different droplet materials can be used as a promising method for 3D microfabrication in the future.